Improving Science Literacy and Student Learning Outcomes Through the Ethnoscience-Based PJBL Model in Elementary Schools - faiqi, Erina dini; sama, sama; shiddiq, Ahmad (JUPE : Jurnal Pendidikan Mandala, 2025)
Science literacy is one of the basic skills to compete in an increasingly competitive life. However, Indonesian students still have a low level of science literacy. This study aims to determine the differences in science literacy and cognitive learning outcomes of students in the experimental and control classes and to determine students' responses to the ethnoscience-based PjBL model in learning. This quasi-experimental study used a non-equivalent control group design. The research sample was students of SDN Karduluk 2 Sumenep. Data collection was carried out using test and non-test methods. The instruments used were science literacy and cognitive learning outcomes tests and response questionnaires as non-test instruments. Data analysis was carried out using descriptive and inferential analysis. The results showed significant differences in science literacy and cognitive learning outcomes between students in the experimental and control classes. The ethnoscience-based PjBL model received an excellent response. This study concludes that the ethnoscience-based PjBL model can improve students' science literacy and cognitive learning outcomes. This study contributes to chemistry learning by improving science literacy and learning outcomes through the ethnoscience-based PjBL model.